Connection of Investment Activity and Digitalization in the Megacities of the Republic of Kazakhstan - L. M. Bekenova; V. A. Korvyakov; I. M. Drapkin (Экономика: стратегия и практика)
The purpose of the article is to study the influence of digitalization factors on the investment activity of the largest cities of the Republic of Kazakhstan. During the research, the methods of correlation analysis, indexing, comparison, generalization, and synthesis were applied. The scientific novelty of the study lies in assessing the impact of digitalization on the investment potential of cities. The authors selected and analyzed indicators for assessing the level of digitalization of the megalopolises of the Republic of Kazakhstan; the methodology was modified and the level of digitalization of cities of republican significance of the Republic of Kazakhstan was assessed, conclusions were drawn about the current and future potential of digitalization as a factor in increasing the investment attractiveness of these cities. General conclusions were made that for Almaty and Nur-Sultan, digitalization is already a good factor in attracting investment, while Shymkent needs enhanced development of digital infrastructure for it to become a factor in increasing investment activity in the city. The research results can be used both in the formation of long-term plans for the development of these cities, and as a basis for further research in this direction. Prospects for further research on this topic - in increasing the available reliable and relevant data through the collection of official statistics, expanding the range of digitalization factors affecting investment activity and the use of more comprehensive assessment methods that will determine not only the closeness of the relationship, but also the exact value of the effects of factors each other.